2007
DOI: 10.1074/jbc.m702672200
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Chaperones Reduce Endoplasmic Reticulum Stress and Prevent Mutant HFE Aggregate Formation

Abstract: HFE C282Y, the mutant protein associated with hereditary hemochromatosis (HH), fails to acquire the correct conformation in the endoplasmic reticulum (ER) and is targeted for degradation. We have recently shown that an active unfolded protein response (UPR) is present in the cells of patients with HH. Now, by using HEK 293T cells, we demonstrate that the stability of HFE C282Y is influenced by the UPR signaling pathway that promotes its degradation. Treatment of HFE C282Y-expressing cells with tauroursodeoxych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 30 publications
5
119
0
Order By: Relevance
“…Thus, we treated MAN1A1‐ overexpressing cells with ER stress inhibitors, including the chemical chaperone sodium 4‐phenylbutyrate (4‐PBA) and tauroursodeoxycholic acid (TUDCA), both of which ameliorate ER stress,35 to examine whether they can block or revert the expression of cell cycle‐ and migration‐related genes as well as the UPR regulators in the MAN1A1 ‐overexpressing cells. On treatment with the ER stress inhibitors 4‐PBA and TUDCA, the up‐regulation of these genes was reversed in Hep3B cells, PLC5 cells, HepG2 cells, and 293T cells (Supporting Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we treated MAN1A1‐ overexpressing cells with ER stress inhibitors, including the chemical chaperone sodium 4‐phenylbutyrate (4‐PBA) and tauroursodeoxycholic acid (TUDCA), both of which ameliorate ER stress,35 to examine whether they can block or revert the expression of cell cycle‐ and migration‐related genes as well as the UPR regulators in the MAN1A1 ‐overexpressing cells. On treatment with the ER stress inhibitors 4‐PBA and TUDCA, the up‐regulation of these genes was reversed in Hep3B cells, PLC5 cells, HepG2 cells, and 293T cells (Supporting Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Logically, then, interventions that shift the ER stress-UPR balance towards decreased ER stress might prove useful in the treatment of AMD. A variety of data have demonstrated that chemical and pharmacological chaperones can decrease signs of ER stress [31][32][33]. Taken together, this suggests a potential for such compounds in the treatment of AMD.…”
Section: Er Stress In Amdmentioning
confidence: 88%
“…Both in vivo and in vitro studies of these diseases have elucidated the role of particular chaperone compounds in decreasing misfolded protein aggregation, enhancing proper trafficking of the protein(s) in question to target sites, and ameliorating the overall disease phenotype. The success of chaperones in other disorders, such as nephrogenic diabetes insipidus and Parkinson's disease, is encouraging [21,31,32,38,50]. However, to date, no published studies have examined the use of chemical chaperones as a treatment for AMD in humans or in AMD models.…”
Section: Similarities Between Amd and Other Neurodegenerative Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, at least seven missense mutations causing disease were reported at the HFE exon 4 (which codes for the α3 domain of the protein) including the major p.Cys282Tyr mutation, making this exon a hot spot for mutations. In the case of this mutation, the tyrosine for cysteine substitution disrupts the formation of the disulfide bond that physiologically occurs between Cys225 and Cys282 residues and that is essential for HFE association with β2-microglobulin [1,16,17]. Therefore, the p.Cys282Tyr-mutated HFE protein is unable to bind to the chaperone β2-microglobulin and to be transported to cell surface where it would interact with TfR1 and TfR2 in order to regulate hepcidin expression.…”
Section: Discussionmentioning
confidence: 99%